PHYTOCHEMICAL ANALYSIS OF Mucuna pruriens L. LEAVES EXTRACT AND ITS INHIBITION TEST AGAINST Curvularia lunata (WAKK). BOED. THAT CAUSED LETTUCE LEAF SPOT - I Made Ary Putra Nata; I Ketut Suada; Trisna Agung Phabiola (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2022)
Curvularia lunata is a pathogenic fungi that attack various plant species including lettuce. Its control needs to be carried out in an environmentally friendly manner, namely using botanical fungicides. M. pruriens is a legume plant that is widespread in Indonesia that has a potential as a botanical fungicide, beside as a traditional medicine. The purpose of this study was to study the chemical content of M. pruriens leaves and its potency to inhibit the growth of C. lunata. The determination of the compounds was carried out by Gas Chromatography-Mass Spectrophotometry and the inhibition test was carried out using diffusion well, and agar dillution method. The result showed that the crude extract of M. pruriens leaves contained ethyl isothiocyanate that act as an antifungal with AUC of 20,78%. The MIC of the extract was 0,9%. The extract at 5% concentration was capable to inhibit C. lunata growth, mycelium mass, and conidia production respectively 38,33%; 67,14%; 99,88% compared to control.